Outcomes and Prognostic Factors for Survival of Neonates With Necrotizing Enterocolitis - Siahaan, Elena Sophia Elekta Dilean; Adriansyah, Wahyudhy; Sasmita, Andika Purba; Fauzi, Aditya Rifqi; Dwihantoro, Andi; Gunadi, (Frontiers in Pediatrics, 2021)
Background: Due to the survival of preterm neonates are continually improved, the modifiable prognostic factors of necrotizing enterocolitis (NEC) are essential to be investigated and considered in making a suitable treatment to decrease the prevalence and effect of NEC. Many prognostic factors have been associated with the survival of neonates with NEC; however, the studies show conflicting results. Moreover, the study from developing countries regarding NEC outcomes is minimal. Here, we aimed to determine the survival of neonates with NEC and associate it with the prognostic factors. Methods: A retrospective study was conducted using medical records of neonates with NEC at our institution from January 2014 to December 2019. Results: Fifty-two neonates with NEC were involved with the overall survival of 44.2%. Log-rank analysis showed that NEC staging and birth weight were significantly associated with the survival of neonates with NEC with a p-value of 0.010 and 0.002, respectively, while sex, APGAR score, platelet count and type of treatment were not (p=0.068, 0.752, 0.087, and 0.343, respectively). Multivariate analysis revealed that sex and NEC staging were strongly associated with the survival of neonates with NEC with a p-value of 0.018 (HR=3.10 [95% CI=1.21 – 7.93]) and 0.019 (HR=0.44 [0.22 – 0.87]), respectively. Conclusions: Our study shows that sex and NEC staging might affect the survival of neonates with NEC. It implies that NEC staging should be closely monitored and intervened as early as necessary to prevent further morbidity and mortality.